Does Being Hopeful Make You Green? - Duggal, Vedika (My University, 2023)
This study explored the mediating role of hope between environment identity and pro environment behaviour. A mixed method approach was adopted. A correlational research design was adopted to explore the proposed relationship. This was done in two separate groups of students. One doing a classroom focussed environment course (N=288) of the age group 18-20 years the Engineering students, another doing an experiential oriented environment (N= 188) course, the Management students. In both the groups environment identity was found to be a strong predictor of pro environment behaviour. Role of hope as a mediator was found only in Engineering students . This relationship was further explored in an experimental setting. Three different stories of the environment i.e control, accidental environmentalist and intentional environmentalist were adapted from Sabherwal and Shreedhar (2022). It was found that the three conditions differed across environment identity and pro environment behaviour but not climate change hope. In conclusion, incorporating narrative-based environmental education methods, such as storytelling, can effectively enhance students' environmental knowledge, attitudes, and behaviours, fostering a deeper connection with nature and promoting pro-environmental behaviour.
Keywords: Environment identity; Pro environment Behaviour; Hope; Climate Change; Narratives